2023
DOI: 10.1021/acsomega.2c07875
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Heteroannular Benzoxazole and Benzimidazole Scaffolds via Carbodiimides Using Azide–Isocyanide Cross-Coupling as Catalyzed by Mesoionic Singlet Palladium Carbene Complexes Derived from a Phenothiazine Moiety

Abstract: The coupling of aryl and aliphatic azides with isocyanides yielding carbodiimides (8–17) were efficiently catalyzed by well-defined structurally characterized trans-(MIC)PdI2(L) [MIC = 1-CH2Ph-3-Me-4-(CH2N(C6H4)2S)-1,2,3-triazol-5-ylidene, L = NC5H5 (4), MesNC (5)], trans-(MIC)2PdI2 (6), and cis-(MIC)Pd(PPh3)I2 (7) type palladium complexes, which incidentally mark the first instances of the use of mesoionic singlet palladium carbene complexes for the said application. As observed from the product yields, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Importantly, prompted by this study, efficient means of suppressing the H–CN formation by reaction engineering H–CN scavenging and/or solvent engineering as well as by replacing DIC with TBEC , have been developed. Overall, DIC is nowadays recognized as a universally used CR for ABF (Figure a), and while carbodiimides can be synthesized by a wide variety of methods, , a part of the broad appeal of using DIC in particular is that industrially it is manufactured in a highly scalable and cost-efficient manner by condensation of isopropylamine and i Pr-NCS, which also stems from isopropylamine, followed by a facile dehydrosulfurization of the resulting DITU to furnish the CR (Figure b) . With regards to using DIC in peptide synthesis, we have recently reported that this CR contains a varying amount of sulfur, and that the main S-containing impurity is the thiourea DITU, an intermediate in the route of synthesis (RoS) of DIC .…”
mentioning
confidence: 99%
“…Importantly, prompted by this study, efficient means of suppressing the H–CN formation by reaction engineering H–CN scavenging and/or solvent engineering as well as by replacing DIC with TBEC , have been developed. Overall, DIC is nowadays recognized as a universally used CR for ABF (Figure a), and while carbodiimides can be synthesized by a wide variety of methods, , a part of the broad appeal of using DIC in particular is that industrially it is manufactured in a highly scalable and cost-efficient manner by condensation of isopropylamine and i Pr-NCS, which also stems from isopropylamine, followed by a facile dehydrosulfurization of the resulting DITU to furnish the CR (Figure b) . With regards to using DIC in peptide synthesis, we have recently reported that this CR contains a varying amount of sulfur, and that the main S-containing impurity is the thiourea DITU, an intermediate in the route of synthesis (RoS) of DIC .…”
mentioning
confidence: 99%
“…From the standpoint of cost and sustainability, CDIs are particularly attractive due to the simplicity of their RoS from bulk chemicals, facilitating an affordable supply of CDIs on an industrial scale. Specifically, despite the various approaches for the synthesis of CDIs in the literature, , industrially, CDIs are manufactured practically exclusively by the condensation of an amine with an isothiocyanate followed by dehydrosulfurization (Figure a) . In fact, as isothiocyanates are also made from amines by a reaction with CS 2 , the entire synthesis of CDIs can be accomplished in a practical and atom-efficient manner starting from one or two amines.…”
Section: Introductionmentioning
confidence: 99%